Das condicões de aplicabilidade da teoria do autocuidado em enfermagem obstétrica: sondagem junto à puérpera de parto eutócico - Souza, Ivis Emilia de Oliveira (1987)
The author shows a study realized in maternity hospitais in the city of Rio de Janeiro. The work researches the implantation of the scientific methodology in the attendance of obstetrics nursing, theoretical pattern adopted, advantages and difficulties. Intends yet to verify the possibilities of applicability or implementation of the theory of self-care from Dorothea E.Orem, in obstetrics nursing, through the uprising and analysis of the conditions of the clientele, in consonance with the determinant of activity of self-care. The sample mentions 18 public insti- tutions that performs attendance in internmenfs regimen, and 202 parturientes of eutocic childbirth. The results shows that a reduced number of institutions utilizes some scientific methodology in the nursing attendance to obstetric Client. And show a correlation, positive and significative, between obstetric characteristics and determinants of self-care. Suggests, among other recomendations, a deepening in the methodologic topic and in the theoretical and practical emphasis of the obstetric client.